Baseline Preferences for Daily, Event-Driven, or Periodic HIV Pre-Exposure Prophylaxis among Gay and Bisexual Men in the PRELUDE Demonstration Project - Vaccher, Stefanie J.; Gianacas, Christopher; Templeton, David J.; Poynten, Isobel M.; Haire, Bridget G.; Ooi, Catriona; Foster, Rosalind; McNulty, Anna; Grulich, Andrew E.; Zablotska, Iryna B.; , On Behalf of the PRELUDE Study Team; Carr, Andrew; et al. (Frontiers in Public Health, 2017)
Introduction: The effectiveness of daily pre-exposure prophylaxis (PrEP) is well established. However, there has been increasing interest in non-daily dosing schedules among gay and bisexual men (GBM). This paper explores preferences for PrEP dosing schedules among GBM at baseline in the PRELUDE demonstration project. Materials and Methods: Individuals at high-risk of HIV were enrolled in a free PrEP demonstration project in New South Wales, Australia, between November 2014 and April 2016. At baseline, they completed an online survey containing detailed behavioural, demographic, and attitudinal questions, including their ideal way to take PrEP- daily (one pill taken every day), event-driven (pills taken only around specific risk events), or periodic (daily dosing during periods of increased risk). Results: Overall, 315 GBM (98% of study sample) provided a preferred PrEP dosing schedule at baseline. One-third of GBM expressed a preference for non-daily PrEP dosing; 20% for event-driven PrEP, and 14% for periodic PrEP. Individuals with a trade/vocational qualification were more likely to prefer periodic to daily PrEP (aOR=4.58, 95%CI: [1.68, 12.49]), compared to individuals whose highest level of education was high school. Having an HIV-positive main regular partner was associated with strong preference for daily, compared to event-driven PrEP (aOR=0.20, 95%CI: [0.04, 0.87]). Participants who rated themselves better at taking medications were more likely to prefer daily over periodic PrEP (aOR=0.39, 95%CI: [0.20, 0.76]). Discussion: Individuals’ preferences for PrEP schedules are associated with demographic and behavioural factors that may impact on their ability to access health services and information about PrEP, and patterns of HIV risk. At the time of data collection, there was limited data available about the efficacy of non-daily PrEP schedules, and clinicians only recommended daily PrEP to study participants. Further research investigating how behaviours and PrEP preferences change correspondingly over time is needed.